Rapid and Scalable Synthesis of Mo‐Based Binary and Ternary Oxides for Electrochemical Applications. (29th May 2017) - Qu, Gan; Li, Tianqi; Jia, Shuangfeng; Zheng, He; Li, Lei; Cao, Fan; Wang, Hai; Ma, Wenhao; Tang, Yiwen; Wang, Jianbo
Abstract : Mo‐based binary oxides (MBOs) and Mo‐based ternary oxides (MTOs) are a research focus because of their widespread applications. The traditional synthesis routes for MBOs and MTOs require high temperature and are time intense. Here, a rapid, facile, and scalable strategy to efficiently fabricate MBOs and MTOs with various morphologies and crystal structures is reported. Only 1 min is required for the whole process and the yield is above 90%. This strategy is the simplest and the fastest method reported and exhibits large potential for application. Furthermore, the as‐synthesized H x MoO3 nanobelts and NiMoO4 · x H2 O nanowires display a specific capacitance of 660.3 F g −1 at 2 mV s −1 and a specific capacity of 549 C g −1 at 1 A g −1 . In addition, to assemble the H x MoO3 and NiMoO4 · x H2 O electrodes together, the solid state hybrid electrolyte is employed to take advantage of MBOs and MTOs. The obtained NiMoO4 · x H2 O//H x MoO3 device delivers a specific capacitance of 156 F g −1 at 0.8 A g −1 and an energy density of 55.6 Wh kg −1 at a power density of 640 W kg −1, making it attractive for application as an energy storage material. Abstract : A facile strategy to fabricate Mo‐based binary oxides and Mo‐based ternary oxides simultaneously is reported. This strategy exhibits large potential for industrialization. Moreover, the obtained H x MoO3 nanobelts and NiMoO4 · x H2 O nanowires display outstanding electrochemical performance, acting as negative and positive electrodes correspondingly. Consequently, the assembled NiMoO4 · x H2 O//H x MoO3 device delivers superior energy storage performance.